Earnings conference calls and annual reports, similar or different information? - Kurmanbek Meirkulov; Nicole Pavlides; Maarten Pronk; Erik Roelofsen (MAB)
Nearly half of the questions raised in the Q&A part of earnings conference calls is related to topics which are not discussed in the presentation part. The difference between the Q&A and the annual report is even larger. The majority of topics in the Q&A is not raised in the annual report. Interviews with investor relation officers indicate that they consider the conference calls and annual reports as information channels with a different purpose, where conference calls are meant to inform the markets about the progress in executing the strategy and to reinforce key messages.